Analyse empirique de la relation entre tourisme et compétitivité : l’exemple des Antilles françaises - Louis Dupont (Études Caribéennes)
The tourism competitiveness is an important concept today. The most studies investigate this theme from different ways. However, there are few studies about empirical link between tourism and competitiveness. This paper, thus attempts to examine the empirical relationship between these two variables. It uses the cointegration and error correction model (ECM) in a bivariate context as a precondition to apply Granger causality tests. This procedure was carried out in the case of French West Indies’s tourism industry during 1990-2010. The results show that there is a long-term relationship between tourism and competitiveness. In addition, Granger causality tests reveal no one-directional or bi-directional impact in the case of tourism receipts and GDP. Therefore, tourism-led growth hypothesis (TLG) cannot be inferred for French West Indies’s economy as a major concern of destination managers.